Stages of population geography development: Stages of population geography development (jornal of the libyan geographical society, 2016)
Population geography is a relatively new branch of human geography that studies the multifaceted relationships between humans and their environment. Population is the central focus around which many sciences, both humanistic and applied, revolve. This study encompasses various aspects of population analysis in different environments.Population can be defined as that factor of human geography that represents the specialized variations in demographic characteristics available to population groups, and studies the socio-economic outcomes that differ from one another and the existing geographical conditions in a particular area unit.In addition, population geography is of great importance in studying the development of various demographic aspects at a specific time, or over a specific period of time. If we accept that Trewartha was credited with writing the first article on the subject of population geography in 1953, then the study of population geography branched out and flourished thereafter very quickly and became a fertile field for numerous studies.
Keywords: Population geography; Humanities; Population studies; Various demographic aspects